Breadbox Entreprise / Muhammad Hakim Hisam ... [et al.] - Hisam, Muhammad Hakim; Mohd Zahir, Muhammad Haziq; Khairul Lizam, Hizairi Eimran; Badrol Isa, Adib Farhan; Usuloudin, Aiman Muqhriz (2023)
BreadBox is a new toast shop start-up located in Shah Alam. The menu will include a variety of exceptionally bread toast that are freshly made using locally sourced such as peanut from Selangor establishments. There is also a wide variety of different types of bread toast with meat. The shop will be located in a busy intersection of a highly trafficked area of Shah Alam . It will be surrounded by government office and residence, chain restaurants, and other businesses that are frequented by locals.The design of BreadBox will be comfortable and convenient in order to attract all residents of Shah Alam. The demographic will be residents of the community that come from all different backgrounds and income levels. It will be family-friendly, trendy, and offer a seating area that is able to accommodate multiple seating options. The product offer is toast and savory as well drink. Example toast kaya , Chicken Slices and Coffee. BreadBox will target all residents living in and around Shah Alam. It will appeal to students, families, retirees ,and government employees. Because the food is moderately priced compared to other fast food establishments, all income levels will be able to enjoy the delicious offerings of BreadBox. The sales forecast for 1 month is RM43200.50. The total of the sales forcast for the first year is RM518,406. The total sales forecast will have increment every year. The second year is 10% from first year total sales and 15% increment for third year from second year total sales. BreadBox is owned by Partnership Agreement, Muhammad Hakim is the General Manager of the Breadbox and the task is To plan, implement and control overall management of the business. Then Muhammad Haziq is Administrative Manager and the task to make sure the entire worker get their right such as scheme and insurance, such as EPF and SOCSO and Preparing or updating employment records related to hiring, transferring, promoting and terminating. Hizairi Eimran is Marketing Manager and the task Promote the business, product or services and analysing and improving pricing and marketing strategies. Adib Farhan is Operational Manager and the task is controlling production-related operations involved in the creation of goods and services and make sure the operation process following the correct Standard Operational Procedures (SOP). Aiman Muqhriz is Finacial Manager of the BreadBox and the task is manage the financial and account activities of the company.